From tsotsi to mswenko: South African hip hop’s significance for some black South African men - Hersey, Emily (My University, 2018)
Considered a signifier of the African diaspora, hip hop has been able to manifest itself across the globe. In South Africa, hip hop culture has boomed in recent years. This project seeks to understand the significance of South African hip hop to some Black men in South Africa. From interviews with hip hop artists and industry members, I explored hip hop’s direct and indirect ability to provide livelihoods and entrepreneurship opportunities for some Black South African men. This project also explored the gendered experience of men and their understandings and experiences with socioeconomic inequality and injustices, racism and gender inequality in South African society. This research was conducted through a narrative approach and a critical engagement with participants on the topics at hand which provided an additional space for critical reflexivity on the part of the researcher. This research offered a greater understanding of the social and economic impact this industry has on some Black men and aided in opening up dialogues pertaining to Black masculinity in South Africa.
Research Report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Diversity Studies in the Faculty of Humanities, University of the Witwatersrand, March 2018